Pengaruh Arus Kas Operasi, Nilai Perusahaan, Struktur Modal Dan Ukuran Perusahaan Terhadap Return Saham (Studi Empiris Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2011 2015) - Eka S Sariningsih; Asni Aprilia (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2017)
This study aims to analyze the Influence of Operating Cash Flow, Company Value, CapitalStructure and Firm Size to the Stock Return (Empirical Study on Food and Beverage company listedon Indonesia Stock Exchange during 2011 2015). This study uses 60 samples of food and beveragesfirms that listed in Indonesian Stock Exchange during 2011 to 2015. The sampling method used forthis study is purposive sampling. Type of the data used is secondary data. Data analysis used aredescriptive statistics, classical assumption tests and multiple regression analysis. The analytical toolused is with the help of SPPS scale 24.0. The results of this study are partial or simultaneous nosignificant influence between operating cash flow, company value, capital structure and firm size tothe stock returns.